1993
DOI: 10.1073/pnas.90.16.7804
|View full text |Cite
|
Sign up to set email alerts
|

The ornithine decarboxylase gene is a transcriptional target of c-Myc.

Abstract: Constitutive c-myc expression suppresses cell cycle arrest, promotes entry into S phase, and results in the growth factor-independent expression of ornithine decarboxylase (ODC; EC 4.1.1.17). The ODC gene contains a conserved repeat of the Myc binding site, CACGTG, in intron 1. In this report, we demonstrate that c-Myc is a potent transactivator of ODC promoter-reporter gene constructs in fibrobLsts that requires the CACGTG repeat. These sites conferred Myc responsiveness on heterologous promoter constructs, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
531
2

Year Published

1996
1996
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 690 publications
(557 citation statements)
references
References 20 publications
24
531
2
Order By: Relevance
“…Because very few in situ DNA binding sites for any of these proteins have been characterized (Grandori et al, 1996) and because the E-boxes of acknowledged cmyc transcriptional targets have not been examined for binding by N-myc and L-myc, it is not yet completely clear how in vitro binding site preferences might be related to those favored in vivo. Recent results have shown that L-myc is incapable of activating the ornithine decarboxylase (ODC) promoter (HL Zhang and EVP, unpublished observations), a generally accepted c-myc-responsive target (Bello-Fernandez et al, 1993). This could be explained by preferential DNA binding, by di erential requirements for transcriptional co-activators, or by di erences in strengths of the myc protein transcriptional activation domains (TADs) (Barrett et al, 1992).…”
Section: Erential E Ects Of Myc Proteins On Dna Binding Transcripmentioning
confidence: 99%
See 1 more Smart Citation
“…Because very few in situ DNA binding sites for any of these proteins have been characterized (Grandori et al, 1996) and because the E-boxes of acknowledged cmyc transcriptional targets have not been examined for binding by N-myc and L-myc, it is not yet completely clear how in vitro binding site preferences might be related to those favored in vivo. Recent results have shown that L-myc is incapable of activating the ornithine decarboxylase (ODC) promoter (HL Zhang and EVP, unpublished observations), a generally accepted c-myc-responsive target (Bello-Fernandez et al, 1993). This could be explained by preferential DNA binding, by di erential requirements for transcriptional co-activators, or by di erences in strengths of the myc protein transcriptional activation domains (TADs) (Barrett et al, 1992).…”
Section: Erential E Ects Of Myc Proteins On Dna Binding Transcripmentioning
confidence: 99%
“…Others, however, have not observed such an e ect (Henriksson et al, 1993;Lutterbach and Hann, 1994). Under conditions that may be more physiological, we have stably expressed a double Thr 58 /Ser 62 ?Ala c-myc mutant and measured levels of ornithine decarboxylase (ODC), an enzyme whose gene is generally accepted as being c-myc inducible (Bello-Fernandez et al, 1993). We have observed that this mutant cannot up-regulate endogenous ODC enzyme activity whereas wild-type c-myc does so by fourfold (CEN and EVP, unpublished).…”
Section: Burkitt's Lymphoma (Bl)mentioning
confidence: 99%
“…c-Myc has been demonstrated to enhance transcription of a number of direct target genes including aprothymosin , ornithine decarboxylase (Bello-Fernandez et al, 1993;Wagner et al, 1993), cdc25A (Galaktionov et al, 1996), and MrDb (Grandori et al, 1996). In addition, c-Myc has been demonstrated to repress transcription of the growth arrest genes gas1 (Lee et al, 1997) and gadd45 (Marhin et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…As another possibility, the transcriptional targets of c-Myc might be regulated by Pim-1 kinase, since c-Myc is considered to induce apoptosis by activating the transcription of its target genes (Henriksson and LuÈ scher, 1996). To date, ECA39 (Benvenisty et al, 1992), ornithine decarboxylase (ODC) (Bello-Fernandez et al, 1993), p53 (Reisman et al, 1993), a-prothymosin (Gaubatz et al, 1994), cad (Miltenberger et al, 1995), and Cdc25A (Galaktionov et al, 1996) have been shown to be the genes transcriptionally activated by c-Myc. Among them, Cdc25A cell-cycle phosphatase has only recently been recognized as a candidate mediator molecule of c-Mycmediated apoptosis.…”
Section: Discussionmentioning
confidence: 99%